AFŞİN-ELBİSTAN TERMİK SANTRALI UÇUCU KÜLÜNÜN YOL STABİLİZASYONUNDA ÇEŞİTLİ MALZEMELERLE BİRLİKTE KULLANIMI ÜZERİNE BİR ARAŞTIRMA - ALATAŞ, TANER (Fırat Üniveristesi, 1996)
[Abstract Not Available]
A study on the Use of fly ash of Afşin-Elbistan Thermal Power Plant in road stabilization with some materials
Keywords: İnşaat Mühendisliği; Civil Engineering